PELAKSANAAN PEMBINAAN TERHADAP RESIDIVIS ANAK PELAKU TINDAK PIDANA DI LEMBAGA PEMASYARAKATAN ANAK KLAS IIB PEKANBARU - Sri Intan Wulandari; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The child is a mandate from God Almighty that in itself is attached to the dignity and dignity of a whole person.. Based on Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection is someone who is not yet 18 (eighteen) years old, including children who are still in the womb. Children's rights are part of human rights that must be guaranteed, protected, and fulfilled by parents, family, community, government and the state. As for the purpose of writing this thesis, namely: First, to find out the implementation of coaching carried out by Class IIB Pekanbaru Child Correctional Institution against the recidivism of child offenders. Second, to find out the obstacles in the implementation of guidance on child recidivism perpetrators of crimes. Third, to find out the form of efforts to overcome obstacles in fostering the recidivism of child offenders.This research is a sociological juridical research. Sociological juridical is legal research that uses secondary data as the initial data, which is then followed by primary data or field data, examining the effectiveness of a law and research that wants to find a relationship (correlation) between various symptoms or variables as a data collection tool consisting of studies documents and interviews.The conclusion of this study is, First correctional system is held in order to form correctional prisoners including children who are dealing with the law, should be in the context of coaching between children of perpetrators and repeat perpetrators of criminal offenses. Secondly, the constraints faced by officers of child-specific development institutions (LPKA) Pekanbaru II Class, namely the low level of education of children and the lack of skilled personnel, thus hampering the process of coaching carried out by LPKA and the changing mindset of the perpetrators of criminal offenses. Third, the efforts carried out by the Special Penitentiary Center for Class IIB Pekanbaru Children are by increasing the quality of education and human resources, playing an active role in social activities, treating the same and increasing awareness (monitoring) of the perpetrators of recidivism. The author's suggestion of the problem under study is First For the perpetrator of a crime a child or child who is dealing with the law must be made an effort to restorative justice. Second Pekanbaru Class II B LPKA Officer must further improve the quality of service in fostering children with criminal acts such as, improving the quality of Human Resources, Coaching Facilities, Religious Facilities and so on. Third, the Central Government and Regional Government especially the Ministry of Law and Human Rights Humans must pay more attention to the condition of LPKA Klas IIB Pekanbaru, because in accordance with Law No. 12 of 1995 concerning Correctional Correctional System is organized in order to form a Corrected Community in order to become a complete human being.